CCR5 inhibition in critical COVID-19 patients decreases inflammatory cytokines, increases CD8 T-cells, and decreases SARS-CoV2 RNA in plasma by day 14 - Patterson, Bruce K.; Seethamraju, Harish; Dhody, Kush; Corley, Michael J.; Kazempour, Kazem; Lalezari, Jay; Pang, Alina P.S.; Sugai, Christopher; Mahyari, Eisa; Francisco, Edgar B.; Pise, Amruta; Rodrigues, Hallison; et al. (International journal of infectious diseases, 2021)
•Anti-CCR5 humanized monoclonal antibody restored CD8 counts in COVID patients.•Inversely correlated with decreases in plasma viral load (pVL) by day 14.•CCL5/RANTES up 3–5-fold in mild/moderate patients and >100-fold in critical ones.•First report of highly sensitive, quantitative pVL by ddPCR in COVID patients.•Statistically significant drop in IL-6 by day 14 of treatment. Infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is now a global pandemic. Emerging results indicate a dysregulated immune response. Given the role of CCR5 in immune cell migration and inflammation, we investigated the impact of CCR5 blockade via the CCR5-specific antibody leronlimab on clinical, immunological, and virological parameters in severe COVID-19 patients. In March 2020, 10 terminally ill, critical COVID-19 patients received two doses of leronlimab via individual emergency use indication. We analyzed changes in clinical presentation, immune cell populations, inflammation, as well as SARS-CoV-2 plasma viremia before and 14 days after treatment. Over the 14-day study period, six patients survived, two were extubated, and one discharged. We observed complete CCR5 receptor occupancy in all donors by day 7. Compared with the baseline, we observed a concomitant statistically significant reduction in plasma IL-6, restoration of the CD4/CD8 ratio, and resolution of SARS-CoV2 plasma viremia (pVL). Furthermore, the increase in the CD8 percentage was inversely correlated with the reduction in pVL (r = −0.77, p = 0.0013). Our study design precludes clinical efficacy inferences but the results implicate CCR5 as a therapeutic target for COVID-19 and they form the basis for ongoing randomized clinical trials.